Insights Into Mechanisms of Antimicrobial Photodynamic Action Toward Biofilms Using Phenalen-1-One Derivatives as Photosensitizers - Muehler, Denise; Rupp, Christina M.; Keceli, Sercan; Brochhausen, Christoph; Siegmund, Heiko; Maisch, Tim; Hiller, Karl-Anton; Buchalla, Wolfgang; Cieplik, Fabian (Frontiers in Microbiology, 2020)
In view of increasing resistance against antibiotics and antiseptics, antimicrobial photodynamic therapy (aPDT) may be a promising approach for use in dentistry. The aim of this study was to investigate the mechanism of action of aPDT with the phenalene-1-one derivatives SAPYR and SA-PN-05 as photosensitizers by evaluating bacterial ability to replicate, membrane integrity, metabolic activity, and formation of reactive oxygen species (ROS) in biofilms of Actinomyces naeslundii, Streptococcus mutans and Escherichia coli. Single-species biofilms (Actinomyces naeslundii DSM43013; Streptococcus mutans DSM20523 and Escherichia coli DSM1103) were cultured under aerobic conditions for 48 h followed by treatment with the photosensitizers SAPYR and SA-PN-05 at various concentrations (0, 50, 100, 500 μM) and different incubation periods of 5, 10, 20 and 30 min and subsequent irradiation for 10 min (Waldmann PIB 3000; em = 360-600 nm; 50 mW/cm2; 30 J/cm2). Control samples were treated with dH2O and kept in dark for the same periods. Bacterial ability to replicate was evaluated by CFU assay. The cytoplasmic membrane integrity was investigated by flow cytometry using SYBR Green and propidium iodide and visualized by scanning and transmission electron microscopy. For SAPYR, metabolic activity and formation of intracellular ROS after irradiation were evaluated via luminescence and fluorometric assays, respectively. SAPYR showed antimicrobial effects (> 3 log10 CFU reduction) on S. mutans after 5 min and on A. naeslundii after 20 min incubation periods and light activation. For E. coli, CFU reduction was > 2 log10 after 30 min of incubation. SA-PN-05 showed an antimicrobial effect after 5 minutes for all bacteria. Membrane damage upon aPDT with SAPYR was observed for E. coli, but not for S. mutans and A. naeslundii. Following treatment with SA-PN-05, irradiated samples and dark controls of all three species showed loss of membrane integrity. Luminescence and fluorometric assays showed a reduction in metabolic activity and an increase in formation of intracellular ROS in all three species upon aPDT treatment with SAPYR. The observed loss in ability to replicate upon aPDT with SAPYR in single-species biofilms may be due to an increase in formation of intracellular ROS upon photodynamic treatment.